Influence of Handrim Wheelchair Propulsion Training in Adolescent Wheelchair Users, A Pilot Study - Dysterheft, Jennifer L.; Rice, Ian M.; Rice, Laura A. (Frontiers in Bioengineering and Biotechnology, 2015)
Ten full time adolescent wheelchair users (ages 13-18) completed a total of three propulsion trials on carpet and tile surfaces, at a self-selected velocity, and on a concrete surface, at a controlled velocity. All trials were performed in their personal wheelchair with force and moment sensing wheels attached bilaterally. The first two trials on each surface were used as pre-intervention control trials. The third trial was performed after receiving training on proper propulsion technique. Peak Resultant Force, Contact Angle, Stroke Frequency, and Velocity were recorded during all trials for primary analysis. Carpet and tile trials resulted in significant increases in Contact Angle and Peak Total Force with decreased Stroke Frequency after training. During the velocity controlled trials on concrete, significant increases in Contact Angle occurred, as well as decreases in Stroke Frequency after training. Overall, the use of a training video and verbal feedback may help to improve short term propulsion technique in adolescent wheelchair users and decrease the risk of developing upper limb pain and injury.